SETTING A POSITIVE AGENDA FOR INTERNET GOVERNANCE AT THE WORLD SUMMIT ON THE INFORMATION SOCIETY (WSIS): OF TECHNOLOGY AND HUMANKIND - Maurushat, Alana (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2005)
Internet Governance emerged as a contentious and key issue at the 2003 World Summit on the Information Society (WSIS) in Geneva. Against the backdrop of digital solidarity – the benefits of the Information Society should be shared amongst citizens of both developed and developing countries to ensure fair and equitable development for all – the author advocates the need for Civil Society to work together to develop a unified voice and a consolidated list of critical issues. The author provides an overview of some of the contentious issues leading up to the Geneva Phase of WSIS. The author also looks at some of the issues addressed in two critical meetings following the Geneva Summit: The International Telecommunication Union Workshop on Internet Governance (ITU Workshop) and the United Nations Information and Communications Technologies Task Force Global Forum on Internet Governance (UN Global Forum). This is followed by an analysis and discussion of what the author perceives to be the most important issues on Internet Governance from the perspective of enhancing human rights and promoting human dignity in the Information Society. The author identifies three prominent issues: appropriate and effective capacity building, language and cultural rights in the domain name system, and a cautionary approach to model laws which could impact on human rights. The author concludes by offering a strategy on how civil society can be most effective in its contribution to Internet Governance issues for the upcoming WSIS meeting in Tunis.